Subtype-selective effect and molecular regulation of celastrol and triptolide at human nicotinic acetylcholine receptors - Moon, Myungmi; Pyeon, Minsu; Yang, Jaehui; Yun, Jeongyeon; Yeom, Hye Duck; Lee, Mee-Hyun; Lee, Gihyun; Lee, Junho H. (Chemico-biological interactions, 2025)
Celastrol and triptolide, bioactive compounds isolated from Tripterygium wilfordii Hook F, have demonstrated significant pharmacological effects across various biological pathways, making them subjects of extensive research for potential therapeutic applications. Celastrol and triptolide are known to have therapeutic use in neurodegenerative diseases including Alzheimer's disease and Parkinson's disease through neuroprotective action. Nicotinic acetylcholine receptors (nAChRs) are a subtype of cholinergic receptors and are ligand-gated ion channels that play an essential role in regulating synaptic transmission in the central nervous system. The results of this study indicate that celastrol and triptolide inhibit nAChR subtypes in a subtype-specific manner. This inhibitory effect was shown to be reversible, concentration-dependent, and noncompetitive. Mutation experiments were then performed to identify mutations in the binding site of nAChR determined by molecular docking studies and prioritize them based on binding energy, and it was found that triptolide had no inhibitory effect in double mutants of nAChR. These findings confirm that celastrol and triptolide selectively and effectively inhibit α3β2 and α3β4 nAChRs among various nAChR subtypes, and that celastrol and triptolide interact with a specific region of α3β4 nAChRs, which play a key role in the autonomic nervous system, without inhibiting the activity of α7 and α4β2, which act in neurodegenerative diseases. [Display omitted] •Celastrol and triptolide inhibit nicotinic acetylcholine receptor in a subtype-specific manner.•This inhibitory effect was shown to be reversible, concentration-dependent, and noncompetitive.•Triptolide interacted with α3 (Y151) or β4 (N111) subunits.